SYMBOLS AND POWER IN THE MASCOT DESIGN OF FTPM MAN: A ROLAND BARTHES SEMIOTIC ANALYSIS IN THE CONTEXT OF THE ‘SHOW YOUR ART EXPRESSION UNDER THE SEA’ FESTIVAL - Qadar Basri, Syaiful; Sabri, Indar (Institut Seni Indoensia Surakarta, 2025)
This paper aims to analyze the icon design of Festival Teater Pelajar dan Mahasiswa Nasional (FTPMN) 2024 with the title “Show Your Art Expression Under the Sea” through Roland Barthes' semiotic approach. The focus of the paper is to reveal the denotation, connotation, and mythical meanings contained in the icon design, as well as how this icon strengthens the festival's identity as a forum for student artistic expression. The research method used is qualitative with descriptive analysis of the visual elements of the icon, including colors, shapes, and symbols. The results showed that the 2024 (FTPMN) icon design not only represented the theme of the sea, but also implied the values of freedom of expression, collaboration, and cultural diversity. The conclusion of this research confirms that icon design acts as an effective visual communication tool in building the image and spirit of the festival.